Acorn woodpeckers vocally discriminate current and former group members from nongroup members. (18th June 2020) - Pardo, Michael A; Hayes, Casey E; Walters, Eric L; Koenig, Walter D
Abstract: In species with long-term social relationships, the ability to recognize individuals after extended separation and the ability to discriminate between former social affiliates that have died and those that have left the group but may return are likely to be beneficial. Few studies, however, have investigated whether animals can make these discriminations. We presented acorn woodpeckers ( Melanerpes formicivorus ), a group-living, cooperatively breeding bird, with playbacks of current group members, former group members still living nearby, former group members that had died or left the study area, and familiar nongroup members. Subjects responded more quickly to the calls of nongroup members than to the calls of current group members or former group members still living in the study area but did not discriminate between nongroup members and former group members that had died or disappeared. This suggests that acorn woodpeckers can vocally recognize both current group members and former group members that have dispersed to nearby groups and that they either forget former group members that no longer live in the vicinity or classify them differently from former group members that still live nearby. This study suggests an important role for vocal recognition in maintaining valuable relationships with social affiliates postdispersal. Abstract : We found that acorn woodpeckers, a group-living bird, can recognize the calls of their current group members and former group members that still live nearby but treat the calls of dead former group members like outsiders. We played recordings of current group members, living former members, dead former members, and nonmembers to wild woodpeckers. Subjects responded more quickly to nonmembers and dead former members than to current members and living former members.